The prevalence and correlates of supportive care needs in testicular cancer survivors: a cross‐sectional study. Issue 11 (3rd July 2013) - Smith, Allan 'Ben'; King, Madeleine; Butow, Phyllis; Luckett, Tim; Grimison, Peter; Toner, Guy C.; Stockler, Martin; Hovey, Elizabeth; Stubbs, John; Hruby, George; Gurney, Howard; Turner, Sandra; et al.
Abstract: Objective: This cross‐sectional study aimed to identify the prevalence and correlates of supportive care needs in testicular cancer (TC) survivors. Methods: Men who had completed active anti‐cancer treatment for TC between 6 months and 5 years previously showing no evidence of recurrence were recruited from 14 Australian cancer centers (September 2009–February 2011). Participants completed a self‐report questionnaire measuring sociodemographics, disease, and treatment information, supportive care needs (CaSUN), psychological distress (DASS21) and health‐related quality of life (HRQoL; SF36v2). Results: Of the 486 eligible TC survivors invited to participate, 244 completed the questionnaire. Sixty‐six percent reported one or more unmet supportive care needs. The mean number of unmet needs was 4.73 (SD = 7.0, Range = 0–34). The most common unmet needs related primarily to existential survivorship issues (e.g., life stress) and relationships (e.g., sex life). Younger age and presence of chronic illness other than TC were significantly associated with higher number of unmet needs. The number of unmet needs was more highly correlated with psychological distress and HRQoL than unmet need strength. Conclusions: The majority of TC survivors reported one or more unmet needs. Unmet needs regarding existential survivorship issues were frequently reported by TC survivors despite their favorable prognosis. Relationships unmet needs were less prevalent but still more common than in breast and gynecological cancer survivors. These findings appear to be related to the young age of TC survivors. As a higher number of unmet needs is significantly associated with psychological morbidity and impaired HRQoL, interventions addressing this constellation of issues are needed. Copyright © 2013 John Wiley & Sons, Ltd.